Unveiling shear-induced non-uniform deformation of segmented tunnels through fully instrumented model tests - Yi Zhou; Hong-Hu Zhu; Dao-Yuan Tan; Jing-Wu Huang; Zhen-Rui Yan; Wan-Huan Zhou (Tunnelling and Underground Space Technology, 2026)

Novel non-thermal plasma based strategy to synthesize high-performance multistage mesoporous cobalt-ceria oxides for plasma-catalytic decomposition of environmentally hazardous acetone - Lu Liu; Jian-hua Liu; Zhen-yun Wang; Guang-cai Shao; Yan-gang Hu; Karen Leus; Jian-li Mi; Chuan-long Ma; Rui-tang Guo; Qing-shan Wang; Anton Nikiforov; Pascal Van Der Voort; et al. (Journal of Hazardous Materials, 2026)

Cellulose nanocrystal-based antimicrobial porous foam loaded with cinnamaldehyde for enhanced chilled meat preservation - Jin-ling Wu; Ai-ling Zhong; Rui Zhang; Hai-yan Huang; Teng-gen Hu; Zhen-lin Xu; Hong Wang; Peng Wen (Food Packaging and Shelf Life, 2026)

Metabolic inflexibility across heart failure phenotypes: mechanisms and type-specific therapeutic implications - Li Chen; Xin-Rui Yang; Yan Jiang; Shi-Qi Cheng; Zhen-Xun Wan; Jin-Wen Wu; Ming-Tai Chen; Yuan-Yuan Li; Gang Luo; Meng-Nan Liu (Apoptosis, 2026)

Extreme rainfall intensifies nitrogen responses through baseflow in arid and semi-arid river basins - Jinghui Dou; Rui Xia; Zixuan Tang; Zhen Huang; Xiaohui Jiang; Kai Zhang; Lina Li; Chao Yan (Journal of Hydrology, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Start-up and operational strategies for side-stream nitrification reactors in a cyclic up-concentration nitrogen recovery process: Enhancing targeted nitrate conversion and deciphering nitrogen metabolism - Molin Lian; Zihang Ma; Guang Chen; Xiangdong Xu; Rui Tang; Shikun Yan; Yu Wang; Yuyue Zhang; Zhen Zhou (Chemical Engineering Journal, 2025)

Frititaipaines A−O, undescribed cevanine-type isosteroidal alkaloids from the bulbs of Fritillaria taipaiensis and their anti-neuroinflammatory and AChE inhibitory activities - Zai-Long Huang; En-Ke Qu; Lan-Run Yang; Rui Luo; Yan-Ni Liang; Shi-Jun Liu; Yuan-Zhen Xu; Dong-Bo Zhang (Phytochemistry, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Dithiothreitol oxidative potential (OP) of PM2.5 in Beijing: Quantitative contribution of metals to OP and its prediction based on machine learning models - Yusheng Ma; Mengshuang Sheng; Jing Shang; Rui Tang; Jiong Cao; Yuhan Liu; Chenyu Liang; Yu Kuang; Yan Zheng; Zhen Cheng; Rico K.Y. Cheung; Robin L. Modini; et al. (Journal of Hazardous Materials, 2025)

A salt-tolerant tetracycline degrading fungal strain of Candida palmioleophila: Characterization and degradation pathway - Zhen-Ying Li; You-Wei Cui; Hui-Juan Yan; Hui-Kai Liang; Rui-Chun Yang (Journal of Hazardous Materials, 2025)

6,7-Dimethoxy-3H-Quinazolin-4-One as a dual-function inhibitor of polyphenol oxidase and bacteria: biological evaluation, mode of action, and anti-browning studies - Xiu-Zhen Li; Jin-Rui Qiao; Yi-Rui Wu; Dong-Yan Zhou; Yu-Dan Shi; Shu-Meng Zhu; Qiu-Han Bai; Xiao-Lei Xia; Wei-Ming Chai (Food Bioscience, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Tetracycline degradation by a mixed culture of halotolerant fungi-bacteria under static magnetic field: Mechanism and antibiotic resistance genes transfer - Zhen-Ying Li; You-Wei Cui; Hui-Kai Liang; Hui-Juan Yan; Rui-Chun Yang (Journal of Hazardous Materials, 2025)

A compact autonomous inspection system for greenhouse environmental information sensing and three-dimensional visualization - Rui Yan; Xiangnan He; Zhen Wang; Yuting Wang; Zhemin Li; Xian Li (Computers and Electronics in Agriculture, 2025)

Diatomic "catalytic/co-catalytic" Fe/Mo catalysts promote Fenton-like reaction to treat organic wastewater through special interfacial reaction enhancement mechanism - Zhen Liu; Xin-Yi Xu; Fei Xu; Rui-Dian Su; Bin Li; Fang Zhang; Xing Xu; Yan Wang; De-Fang Ma; Bao-Yu Gao; Qian Li (Water Research, 2025)

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Regulation roles of dre-miR-187 in neurological damage by low concentration toluene in zebrafish - Shu-Hui Men; Jia-Yun Xu; Zhen-Guang Yan; Jin-Zhe Du; Ming-Rui Li; Zi-Ye Wang; Chen Liu; Xin Zheng (Journal of Cleaner Production, 2025)

TDCPP promotes apoptosis and inhibits the calcium signaling pathway in human neural stem cells - Ming-Rui Li; Guo-Rui Zhou; Zi-Ye Wang; Bo-Yang Li; Shu-Hui Men; Zhen-Guang Yan (Science of The Total Environment, 2025)

The long noncoding RNA ALEX1 confers a functional phase state of ARF3 to enhance rice resistance to bacterial pathogens - Meng-Qi Lei; Rui-Rui He; Yan-Fei Zhou; Lu Yang; Zhen-Fei Zhang; Chao Yuan; Wen-Long Zhao; Yu Cheng; Jian-Ping Lian; Yu-Chan Zhang; Wen-Tao Wang; Yang Yu; et al. (Molecular Plant, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Formation and evolution of thermokarst landslides in the Qinghai-Tibet Plateau, China - Tao Wei; Hao Wang; Peng Cui; Yan Wang; Bo Zhang; Rui-Long Wei; Zhen-Xing Liu; Chao-Yue Li (Science of The Total Environment, 2024)

Vitrification cryo-foil method for shoot tip cryopreservation and virus eradication in apple - Min-Rui Wang; Jun-Hua Bao; Xiao-Yan Ma; Zi-Han Yan; Zhen-Hua Cui; Li-Ying Zhu; Dong Zhang; Qiao-Chun Wang (Cryobiology, 2024)

Complete genome sequence of the 4-hydroxybenzoate-degrading bacterium Gymnodinialimonas sp. 57CJ19, a potential novel species from intertidal sediments - Dong-Hui Li; Ning Zheng; Zhen-Hai Liu; Xiao-Rui Dong; Chen Zhao; Shi-Gan Yan; Bin-Bin Xie (Marine Genomics, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

The effects and mechanisms of heat stress on mammalian oocyte and embryo development - L.I. Lang; Zhen-zhen Wang; Bin Liu; S.H.E.N. Chang-qing; T.U. Jing-yi; W.A.N.G. Shi-cheng; L.E.I. Rui-ling; P.E.N.G. Si-qi; X.I.A.O. Xiong; Z.H.A.O. Yong-ju; Xiao-yan Qiu (Journal of Thermal Biology, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Two new sesterterpenoids from Atractylodes japonica Koidz. ex Kitam - Yuan-Yuan Zhou; Zhao Sun; Yan Liu; Zhen-Xing Fang; Hui-Rui Gao; Ning-Yu Liu; Xiao-Juan Zhang; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2024)

Integration of the Metabolome and Transcriptome Reveals Diurnal Variability in the Effects of Melatonin on Salt Tolerance in Maize Seedlings - Jiajie Wang; Di Yan; Zhenzong Lu; Rui Liu; Yue Hong; Ye Wang; Zhen Peng; Chunxin Yu; Yuerong Gao; Ziyan Liu; Liusheng Duan; Runzhi Li (Journal of Plant Growth Regulation, 2024)

Phenolic components from the fruits of Solanum xanthocarpum with anti-inflammatory activity - Yan Liu; Rui Yang; Hai-Dan Zou; Zhen-Peng Xu; Juan Pan; Jia-Tong Wu; Wei Guan; Zhi-Chao Hao; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

The application of human-derived cell lines in neurotoxicity studies of environmental pollutants - Ming-Rui Li; Shu-Hui Men; Zi-Ye Wang; Chen Liu; Guo-Rui Zhou; Zhen-Guang Yan (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Insight into the transformation of 4-hydroxy-3-aminophenylarsonic acid (HAPA) and its mechanisms under simulated sunlight irradiation - Yixin Zhang; Yingjie Yan; Wenjing Bai; Rui Tang; Kuizu Su; Zhen-Hu Hu (Journal of Hazardous Materials, 2024)

A review of the toxic effects of ammonia on invertebrates in aquatic environments - Tian-Xu Zhang; Ming-Rui Li; Chen Liu; Shu-Ping Wang; Zhen-Guang Yan (Environmental Pollution, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

High-throughput calculation of organ-scale traits with reconstructed accurate 3D canopy structures using a UAV RGB camera with an advanced cross-circling oblique route - Shunfu Xiao; Yulu Ye; Shuaipeng Fei; Haochong Chen; Bingyu zhang; Qing li; Zhibo Cai; Yingpu Che; Qing Wang; AbuZar Ghafoor; Kaiyi Bi; Ke Shao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Tetrathiafulvalene as a sustainable cathode with high rate and Long Life-span for aqueous Zinc-ion battery at low temperatures - Jiayao Wang; Xinyi Zhang; Zehua Yan; Zhen Rui; Ze Yang; Yongxin Huang; Wenwen Deng (Chemical Engineering Journal, 2023)

Sulfite altered permanganate effects on acetate-enriched short-chain fatty acids production during sludge anaerobic fermentation - Lijuan Wu; Rui Zhu; Xiaoxia Han; Yan Chen; Zhen Long; Hao Dong; Xiaojiang Chen; Yang Wu; Yinglong Su; Zhengyong Zhang; Jingyang Luo (Bioresource Technology, 2023)

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

Aluminum-activated Malate Transporter 12 is involved in restricting root-to-shoot Cl− transport in Arabidopsis under Cl−-salt stress - Rui-Wen Liu; Jian-Zhen Yuan; Xiao-Yu Li; Yan-Nong Cui; Mei-Mei Cai; Zi-Hua He; Qing Ma (Plant and Soil, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Catalytic Hydroprocessing of White Pine Pyrolysis Bio-Oil over Cobalt-Molybdenum Carbide in a Continuous Packed-Bed Reactor - Rui Li; Zhixin Zhao; Bo Zhang; Xiaozheng Sun; Zhen Zhang; Ying Zhang; Haitao Chen; Qiangu Yan (BioEnergy Research, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

Intracranial Aneurysms: Pathology, Genetics, and Molecular Mechanisms - Zhen Xu; Yan-Ning Rui; John P. Hagan; Dong H. Kim (NeuroMolecular Medicine, 2019)

HprK Xcc is a serine kinase that regulates virulence in the Gram‐negative phytopathogen Xanthomonas campestris - Rui‐Fang Li; Ping Cui; Ping‐Zhen Wei; Xing‐Yan Liu; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2019)
Summary The HprK serine kinase is a component of the phosphoenolpyruvate phosphotransferase system (PTS) of bacteria that generally regulates catabolite repression through phosphorylation/dephosphorylation of the PTS protein PtsH at a conserved serine residue. However, many bacteria do not encode a complete PTS or even have an HprK homologue. Xanthomonas campestris pv. campestris ( Xcc ) is a pathogen that cause black rot disease in crucifer plants and one of the few Gram‐negative bacteria that encodes a homologue of HprK protein (herein HprK Xcc ). To gain insight into the role of HprK Xcc and other PTS‐related components in Xcc we individually mutated and phenotypically assessed the resulting strains. Deletion of hprK Xcc demonstrated its requirement for virulence and other diverse cellular processes associated including extracellular enzyme activity, extracellular‐polysaccharide production and cell motility. Global transcriptome analyses revealed the HprK Xcc had a broad regulatory role in Xcc . Additionally, through overexpression, double gene deletion and transcriptome analysis we demonstrated that hprK Xcc shares an epistatic relationship with ptsH . Furthermore, we demonstrate that HprK Xcc is a functional serine kinase, which has the ability to phosphorylate PtsH. Taken together, the data illustrates the previously unappreciated global regulatory role of HprK Xcc and previously uncharacterized PTS components that control virulence in this pathogen.

Application of Multi-rotor Unmanned Aerial Vehicle Application in Management of Stem Borer (Lepidoptera) in Sugarcane - Xiao-Qiu Zhang; Yong-Jian Liang; Zhen-Qiang Qin; De-Wei Li; Chun-Yan Wei; Jin-Ju Wei; Yang-Rui Li; Xiu-Peng Song (Sugar Tech, 2019)

Cloning and Identification of Differentially Expressed Genes Associated with Smut in Sugarcane - Xiu-Peng Song; Dan-Dan Tian; Ming-Hui Chen; Zhen-Qiang Qin; Jin-Ju Wei; Chun-Yan Wei; Xiao-Qiu Zhang; De-Wei Li; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2018)

Least squares reverse-time migration in the pseudodepth domain and reservoir exploration - Xiao-Dong Sun; Yan-Rui Jia; Min Zhang; Qing-Yang Li; Zhen-Chun Li (Applied Geophysics, 2018)

Variable-grid reverse-time migration of different seismic survey data - Xiao-Dong Sun; Zhen-Chun Li; Yan-Rui Jia (Applied Geophysics, 2017)

Phenylpropanoids from the fruits of Nicandra physaloides and their anti-inflammatory activities - Bing You Yang; Yan Liu; Hai Bing Jiang; Zhen Peng Xu; Rui Guo; Rui Wang; Xiao Mao Li; Hai Xue Kuang (Natural Product Research, 2017)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Impacts of ecological restoration and human activities on habitat of overwintering migratory birds in the wetland of Poyang Lake, Jiangxi Province, China - Chuan-zhun Sun; Lin Zhen; Chao Wang; Bang-you Yan; Xiao-chang Cao; Rui-zi Wu (Journal of Mountain Science, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

A study of perfectly matched layers for joint multicomponent reverse-time migration - Qi-Zhen Du; Rui-Yan Sun; Tong Qin; Yi-Tong Zhu; Li-Fei Bi (Applied Geophysics, 2010)

Scutellarin exerts its anti-hypertrophic effects via suppressing the Ca2+-mediated calcineurin and CaMKII signaling pathways - Zhen-Wei Pan; Ying Zhang; Dong-Hua Mei; Rui Zhang; Jing-Hao Wang; Xiang-Ying Zhang; Chang-Qing Xu; Yan-Jie Lu; Bao-Feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)